2012
DOI: 10.1111/j.1540-6229.2011.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

REIT Dividend Policies and Dividend Announcement Effects During the 2008–2009 Liquidity Crisis

Abstract: Real estate investment trust (REIT) dividend policies and dividend announcement effects during the 2008-2009 liquidity crisis are examined. Multinomial logit results indicate that REITs with higher market leverage or lower marketto-book ratios are more likely to cut dividends, suspend dividends or pay elective stock dividends. These results imply that mitigating going-concern risk is an important motive for REITs adjusting dividend policies during the crisis and support dividend catering theory where investor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 43 publications
3
36
1
1
Order By: Relevance
“…Index and the TOPIX.Total Return (TOPIX TR), which include data on dividends. Case et al (2012aCase et al ( , 2012b and Milunovich and Truck (2013) used similar data to explain the REIT markets. Hence, we shall implement the robustness check by using the price index and the total return index (the dividend yield) shown in Figure 3 Peterson and Hsieh (1997), Karolyi and Sander (1998), Ling et al (2002) and Barkham and Geltner (1995) suggested, as shown in Figure 3(d), that S&P500 and US-NAREIT Price behaved similarly to each other, while Case-Shiller U.S. National Home Price behaved differently.…”
Section: Overview Of the J-reit Marketsmentioning
confidence: 99%
See 3 more Smart Citations
“…Index and the TOPIX.Total Return (TOPIX TR), which include data on dividends. Case et al (2012aCase et al ( , 2012b and Milunovich and Truck (2013) used similar data to explain the REIT markets. Hence, we shall implement the robustness check by using the price index and the total return index (the dividend yield) shown in Figure 3 Peterson and Hsieh (1997), Karolyi and Sander (1998), Ling et al (2002) and Barkham and Geltner (1995) suggested, as shown in Figure 3(d), that S&P500 and US-NAREIT Price behaved similarly to each other, while Case-Shiller U.S. National Home Price behaved differently.…”
Section: Overview Of the J-reit Marketsmentioning
confidence: 99%
“…Studies by Case et al (2012aCase et al ( , 2012b and Chang and Chen (2014) showed that the impact of the 2008 crisis on the REIT's market was observed in US as well as other markets. We should then consider the shock of 2008 crisis on the J-REIT market together with the 2011 earthquake.…”
Section: Parameter Estimates and Dynamic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, by the end of 2009 the average dividend yield had declined to 3.7 percent. In fact, common shareholders witnessed approximately 60 U.S. REITs cut or suspend dividends during 2008 and 2009 (Case et al, 2012). In addition, the share price volatility of public real estate companies has increased dramatically in recent years.…”
Section: Introductionmentioning
confidence: 98%